SPATIAL CHANGE AND URBAN DEVELOPMENT HORIZONS IN THE FACE OF ENVIRONMENTAL CHALLENGES IN THE CITY OF SKIKDA - ALGERIA - Boulainine Ameur,; Bousmaha Ahmed, (International Journal of Innovative Technologies in Social Science, 2025)
This article examines the implications of urban spatial change and the prospects for urban development in Skikda in the light of contemporary environmental challenges. The city of Skikda is the result of the stratification of multiple civilisational periods. The choice of Skikda as an industrial centre in eastern Algeria since the 1970s was a turning point, paving the way for rapid urban expansion and substantial transformations in terms of size and purpose, from an agricultural, commercial and tourist vocation to an industrialised urban centre.The research focuses on examining the consequences of this urban transformation, highlighting its effects on the environment and focusing on the change in environmental indicators. We analyse the results to highlight the discrepancies that have accompanied the different periods of spatial transformation using satellite images with a resolution of 30 M. The article shows the importance of adopting a sustainable approach to urban development horizons in order to meet the contemporary and future challenges of reconciling urban growth, environmental conservation and the protection of the well-being of city residents. In conclusion, the article recommends immediate solutions and an adaptation of planning tools to ensure harmonious and ecologically viable urban development in Skikda.